Changes in the Function of Betawi Traditional Houses in the Setu Babakan Area, Srengseng Sawah Village, South Jakarta - Ilham, Defitra Rahmadya; Kahanna, Mutia; Surayya, Yade (Kirana Publisher (KNPub), 2024)
The research entitled “Changes in the Function of Betawi Traditional Houses in the Setu Babakan Area, Srengseng Sawah Village, South Jakarta”. The purpose of this research is to describe the form of functional changes that occur in Betawi traditional houses in Srengseng Sawah and the factors behind the functional changes in Betawi traditional houses in Srengseng Sawah. The theory used in this research is the theory of social change from Selo Soemardjan which is used to identify the factors that cause changes in function in Betawi traditional houses and the theory of functionalism from Malinowski. This research uses qualitative methods, with data collection techniques based on observation, interviews, and documentation. The results of this study explain the form of functional changes that occur in Betawi traditional houses including the function for the place to carry out the Baturan ceremony, the function for the place to carry out the Bebarit ceremony, the function to hold weddings and circumcisions, the function to distinguish social status, the function to store tools and agricultural products. Furthermore, the factors behind the change in function include religion, economy, lifestyle changes, technological advances, and the division of inheritance.